Financial technologies in personal financial planning: robo-advice vs. human-advice - Waliszewski, Krzysztof; Warchlewska, Anna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
The paper presents the essence of financial technologies in personal financial planning, especially robo-advice. The main aim of the paper is to describe the presumptions for the development of robo-advice. An analysis of robo-advice on personal finance management was made. The analysis was based on a review of the subject literature, and on primary and secondary research. Particular attention was paid to the intensification of activities in the implementation of modern solutions and tools supporting the management of personal finances and the gradual development of robo-advisors. Modern solutions are still struggling with great distrust on the part of their current and potential customers, and the development of modern technologies in liquidity and asset management still requires a human factor.